“I’ll do it tomorrow”: Psychological Inflexibility as mediator for academic procrastination - Bischoff, Franciele; Pacheco, Janaína Thaís Barbosa (Perspectivas em Análise do Comportamento, 2025)
Procrastination is widespread in academic context and has an impact on the health and success of individuals’ academic activities. This article investigated the relationship between depression, anxiety, stress, psychological inflexibility, and procrastination in Brazilian university students and to assess the mediating role of psychological inflexibility in the relationship between depression, anxiety and, stress at procrastination. 309 undergraduate and graduate students completed self-report scales for depression, anxiety, stress, procrastination, and psychological inflexibility. It was observed that procrastination is positively correlated to the other mentioned variables, and that psychological inflexibility plays a mediating role in the relationship between depression, anxiety and stress and procrastination in the sample, with explained variability of 33.53%, 30.56 % and 35.95%, respectively. These findings suggest that professionals can explore interventions aimed to increase psychological flexibility to reduce academic procrastination.